2012
DOI: 10.5018/economics-ejournal.ja.2012-44
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Destination Trips and Tourism Statistics: Empirical Evidences in Sicily

Abstract: The knowledge of the actual magnitude and main features of tourism flows in a given destination is an essential prerequisite for the evaluation of tourism impacts and externalities. Indeed, many pleasure trips are often characterized by the visit to more than a single destination. Although the topic is well-documented in literature, the empirical results are limited to a few pioneering studies. The lack may be attributable to the failure of tourism organizations to collect data on multi-destination trip behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the port is no more than 400 m from the city commercial and historical center. Therefore, during their stop, cruise passengers have the possibility to see the main attractions of the city or to take part in tours organized by the cruise companies, and can visit some important destinations near Palermo, such as Monreale with its famous Cathedral, the Valley of the Temples in Agrigento (included in the UNESCO World Heritage List since 1977), or Cefalù, one of the most important international tourist destinations in Sicily (Parroco, Vaccina, De Cantis, & Ferrante, 2012). Fig.…”
Section: Study Contextmentioning
confidence: 98%
“…Moreover, the port is no more than 400 m from the city commercial and historical center. Therefore, during their stop, cruise passengers have the possibility to see the main attractions of the city or to take part in tours organized by the cruise companies, and can visit some important destinations near Palermo, such as Monreale with its famous Cathedral, the Valley of the Temples in Agrigento (included in the UNESCO World Heritage List since 1977), or Cefalù, one of the most important international tourist destinations in Sicily (Parroco, Vaccina, De Cantis, & Ferrante, 2012). Fig.…”
Section: Study Contextmentioning
confidence: 98%
“…Second, while on a trip a visitor might stay in more than one collective accommodation, resulting in an overestimation of the number of visitors (i.e. the ''double counting effect'') and in an underestimation of the total duration of the trip (Lickorish, 1997;Parroco, Vaccina, De Cantis, & Ferrante, 2012;Pearce, 1995). Moreover, the magnitude of this phenomenon strongly depends on tourist mobility within and between destinations, and on the geographical level considered, since the ''double counting effect'' increases as the geographical scale decreases.…”
Section: The Actual Limits Of Tourism Statistics In Europementioning
confidence: 99%
“…The spatial distribution of tourists represents the second main strand of research for tourism in Sicily. In particular, mobility of incoming tourism has been investigated to analyze the competitiveness of Sicilian tourism destinations (Oliveri et al, 2012), to quantify the main implications of multi-destination trips in Sicily both on tourism statistics and on destination management (Parroco et al, 2012a(Parroco et al, , 2012b, to define a territorial network of tourism demand in Sicily (D'Agata et al, 2013), and to explore the issue of unobserved tourism and estimate the actual magnitude of tourism flows in the island (De Cantis et al, 2015). Two isolated case studies have identified and examined which factors have helped rural communities to successfully develop agritourism (Privitera, 2010), and the main determinants of tourism in Sicily (Provenzano, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%